A hypomorphic allele of telomerase uncovers the minimal functional length of telomeres in Arabidopsis. Issue 2 (4th August 2021) - Watson, J Matthew; Trieb, Johanna; Troestl, Martina; Renfrew, Kyle; Mandakova, Terezie; Fulnecek, Jaroslav; Shippen, Dorothy E; Riha, Karel
Abstract: Despite the essential requirement of telomeric DNA for genome stability, the length of telomere tracts between species substantially differs, raising the question of the minimal length of telomeric DNA necessary for proper function. Here, we address this question using a hypomorphic allele of the telomerase catalytic subunit, TERT. We show that although this construct partially restored telomerase activity to a tert mutant, telomeres continued to shorten over several generations, ultimately stabilizing at a bimodal size distribution. Telomeres on two chromosome arms were maintained at a length of 1 kb, while the remaining telomeres were maintained at 400 bp. The longest telomeres identified in this background were also significantly longer in wild-type populations, suggesting cis -acting elements on these arms either promote telomerase processivity or recruitment. Genetically disrupting telomerase processivity in this background resulted in immediate lethality. Thus, telomeres of 400 bp are both necessary and sufficient for Arabidopsis viability. As this length is the estimated minimal length for t-loop formation, our data suggest that telomeres long enough to form a t-loop constitute the minimal functional length.